(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article approaches the play Lazzaro (1948), one of the first works by playwright Francisco Pereira da Silva, born in Piaui, Brazil, in which he uses the genre intermezzo interlaid in an essentially tragic work, in order to discuss its dramatic function in it. The play here analyzed presents many connections with the tragedy Electra in the versions of both Sophocles and Euripides. But while in the Greek plays Orestes is not an instrument of blind fate since he acts as his father’s conscious avenger and his sister’s protector, in Pereira da Silva’s work the text is a little more complex because it is mixed with other texts, be it with different Greek myths or other textual inspirations such as the New Testament. It suffices to pay attention to the character’s given name that is also the title of the play. Besides, in the Brazilian playwright’s work we find the transposition of the original myth to the home of a decaying family in Northeastern Brazil.